2015
DOI: 10.1136/bmjopen-2015-008938
|View full text |Cite
|
Sign up to set email alerts
|

Should HFE p.C282Y homozygotes with moderately elevated serum ferritin be treated? A randomised controlled trial comparing iron reduction with sham treatment (Mi-iron)

Abstract: IntroductionHFE p.C282Y homozygosity is the most common cause of hereditary haemochromatosis. There is currently insufficient evidence to assess whether non-specific symptoms or hepatic injury in homozygotes with moderately elevated iron defined as a serum ferritin (SF) of 300–1000 µg/L are related to iron overload. As such the evidence for intervention in this group is lacking. We present here methods for a study that aims to evaluate whether non-specific symptoms and hepatic fibrosis markers improve with sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…found that the injection of recombinant ferritin helped inhibit bacterial growth in the silkworm Bombyx mori by limiting the iron level in the hemolymph. Similar results have indicated that ferritin expression is upregulated in response to pathogen challenges in the swallowtail butterfly Papilio xuthus (Lepidoptera), 22 the beetle Tribolium castaneum (Coleoptera), 23 the bumblebee Bombus ignitus (Hymenoptera), 24 the horseshoe crab Limulus (Merostomata) 25 and the ark shell Scapharca broughtonii (Lamellibranchia) 26 . Taken together, these findings indicate that ferritin can function as an acute antibiotic protein by storing iron in host cells to inhibit pathogen growth.…”
Section: Introductionsupporting
confidence: 68%
“…found that the injection of recombinant ferritin helped inhibit bacterial growth in the silkworm Bombyx mori by limiting the iron level in the hemolymph. Similar results have indicated that ferritin expression is upregulated in response to pathogen challenges in the swallowtail butterfly Papilio xuthus (Lepidoptera), 22 the beetle Tribolium castaneum (Coleoptera), 23 the bumblebee Bombus ignitus (Hymenoptera), 24 the horseshoe crab Limulus (Merostomata) 25 and the ark shell Scapharca broughtonii (Lamellibranchia) 26 . Taken together, these findings indicate that ferritin can function as an acute antibiotic protein by storing iron in host cells to inhibit pathogen growth.…”
Section: Introductionsupporting
confidence: 68%
“…suggest the potential benefit of early treatment in patients with SF concentrations between the upper limit of normal and 1000 μg/L. Due to confounders and the lack of a randomised clinical trial, the potential benefit of treatment for patients with a mild to moderate iron burden awaits validation . The presence of clinical symptoms is not a prerequisite for diagnosis or treatment.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…1214 However, there is limited evidence on whether patients with only moderately elevated SF (300–1,000 μg/l) benefit from phlebotomy and whether the optimal target should be <300 μg/l (the upper limit of the clinically normal range) or <100 μg/l. The results of a randomized controlled trial comparing iron reduction by erythrocytapheresis with sham treatment by plasmapheresis, 23 which will be available later this year, will for the first time provide high-quality evidence to answer this question.…”
Section: Introductionmentioning
confidence: 99%